Possession, occupation and registration: recombinant ownership in the settler colony. (2nd April 2016) - Bhandar, Brenna
Abstract : No other aspect of property so infuses our social, psycho-symbolic, cultural and political realms as the idea of possession. Whether considering modern theories of subjectivity, relationships between people (from labour relations to intimate ones of love and affection), or indeed, what it means to own something, possession – as an amalgam of both spirit and fact – structures our thought, emotions and actions. The idea of self-ownership, whether in a Lockean vein or as a dialectical struggle for mastery over one's self in relation to an other, persists across a wide spectrum of philosophical discourses on subjectivity; particularly among those in which propriety and impropriety, appropriation and dispossession, and forms of status are acknowledged as central aspects of contemporary social relations and political subjectivity.